Association of climate factors and air pollutants with pneumonia incidence in Lampang province, Thailand: findings from a 12-year longitudinal study - Apaporn Ruchiraset (2020)
© 2020, © 2020 Informa UK Limited, trading as Taylor & Francis Group. This study attempted to understand the associations between pneumonia, climate, and environmental air pollutants in Thailand. A 12-year longitudinal study was performed between 2003 and 2014 in Lampang province, the Northern region of Thailand. Spearman correlation and negative binomial regression modelling were used to explore the relationships between climate factors and environmental air pollutants and pneumonia incidence. Spearman correlation shows that pneumonia incidence was positively correlated with humidity and negatively correlated with temperature, NO2, and O3. The regression modelling produced a series of models to predict pneumonia incidence based on information on climate and air quality. The result of the models shows that humidity and PM10 were associated with pneumonia incidence. To better protect the health, public health policy and risk assessment approach for pneumonia incidence should include considerations of the effect of air pollution. This result can be used for further intervention to take care of human health.